Emotional processing and antidepressant action. - Harmer, C (2013)
Negative affective schema and associated biases in information processing have long been associated with clinical depression. Such an approach has guided the development of successful psychological therapies for this and other emotional disorders. However, until quite recently, there has been a large chasm between the practitioners and scientists working with this approach and those working on the neurobiological basis of depression and its treatment. Recent research, however, has started to bridge this gap and our understanding of the neural processes underpinning these cognitive processes has progressed markedly over the past decade. Moreover, rather than representing separate targets for psychological and biological treatments, novel findings suggest that pharmacological interventions for depression also modify these psychological maintaining factors early in treatment and may be involved in the later emergence of clinically relevant change. Such findings offer the possibility of greater integration between psychological and pharmacological conceptualisations of psychiatric illness and provide an experimental medicine model to generate and test specific predictions. Such a model could be applied to improve treatment development, stratification and combination approaches for patients with depression and provide a framework for considering and overcoming treatment nonresponse.